2014
DOI: 10.1371/journal.pone.0098293
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Druggable Cancer Driver Genes Amplified across TCGA Datasets

Abstract: The Cancer Genome Atlas (TCGA) projects have advanced our understanding of the driver mutations, genetic backgrounds, and key pathways activated across cancer types. Analysis of TCGA datasets have mostly focused on somatic mutations and translocations, with less emphasis placed on gene amplifications. Here we describe a bioinformatics screening strategy to identify putative cancer driver genes amplified across TCGA datasets. We carried out GISTIC2 analysis of TCGA datasets spanning 14 cancer subtypes and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
120
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 56 publications
10
120
0
Order By: Relevance
“…We have shown previously that increased neddylation activity resulting from overexpression of SCCRO promotes oncogenesis in vitro and in vivo (30). In primary tumors, the oncogenic activity of SCCRO is promoted by amplification that is present in many types of cancers, including lung, ovarian, head and neck, and esophageal cancers (35)(36)(37). Interestingly, we found that transgenic expression of UBA domain mutants of SCCRO was more oncogenic than that of wild-type SCCRO.…”
Section: Discussionmentioning
confidence: 66%
“…We have shown previously that increased neddylation activity resulting from overexpression of SCCRO promotes oncogenesis in vitro and in vivo (30). In primary tumors, the oncogenic activity of SCCRO is promoted by amplification that is present in many types of cancers, including lung, ovarian, head and neck, and esophageal cancers (35)(36)(37). Interestingly, we found that transgenic expression of UBA domain mutants of SCCRO was more oncogenic than that of wild-type SCCRO.…”
Section: Discussionmentioning
confidence: 66%
“…However, these technologies have had little impact on standard methods for diagnosis and treatment of HNSCC and many other types of cancer with one or more known mutational or copy number drivers. Despite extensive literature of differential gene expression profiles, mutations and copy number abnormalities in head and neck tumors that could potentially impact future clinical applications, little other than HPV status is done routinely upon diagnosis [7,10,11,13,15,24,32,[35][36][37][38][39][40][41][42][43][44][45][46][47]. A main factor contributing to this lack of progress is that no clear directives or actionable guidelines have been adopted for molecularly profiling HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…All SNVs were assessed for likelihood of clinical relevance based on published literature and public databases including dbSNP, 1000 genome, TCGA and COSMIC [22][23][24]. There were a combined 170 variants (162 HPV-, (purple bars) in the HPV-negative specimens.…”
Section: Mutation Profilingmentioning
confidence: 99%
“…In prostate cancer for example, the EZH2/NSD2 axis confers increased cell proliferation, migration, invasion, stem cell-like properties and tumor growth in a mouse xenograft model [66]. Further studies in prostate cancer have shown that NSD2 acts as a co-activator with NF-κB and androgen receptor [67,68], and regulates the epithelial to mesenchymal transition by dimethylating H3K36 at the TWIST1 locus and activating TWIST1 expression [69].NSD3: frequently overexpressed in diverse tumor types NSD3, also known as WHSC1L1, is overexpressed in cancer [70] and catalyzes mono-and di-methylation at H3K36 in vitro [71]. In cells NSD3 functions as a transcriptional activator, but NSD3's KMTase activity may contribute only partially to its geneactivating role.…”
mentioning
confidence: 99%
“…NSD3 undergoes copy number amplification in 21% of lung squamous cell carcinomas and 15% of breast invasive carcinomas, with a high correlation between copy number and mRNA expression, suggesting that NSD3 may function as an oncogenic driver [70]. Indeed, RNAi knockdown of NSD3 in non-small-cell lung cancer, colorectal cancer, bladder cancer and breast cancer cell lines with NSD3 overexpression causes reduced cell proliferation due to increased apoptosis or cell cycle arrest in the various cancer cell lines [70,75,76]. The breast epithelial cell line MCF10A is normally highly dependent on growth factors and forms small acinar-like structures in 3D Matrigel culture, but these cells can be transformed by expression of NSD3, which confers growth factor-independent proliferation, colony-forming ability in soft agar and expanded and disorganized growth in 3D culture [76].…”
mentioning
confidence: 99%